QUALIDADE AMBIENTAL E SANITÁRIA DAS INDÚSTRIAS DE LATICÍNIOS DO MUNICÍPIO DE MOSSORÓ-RN - Jeronimo, Carlos Enrique; Coelho, Mateus Soares; Moura, Fernanda Negreiros; Araujo, Ana Beatriz Alvez de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705751 The activity of the processing of dairy products constitutes one of the main industrial activities ofthe Brazilian agribusiness. In the state of Rio Grande do Norte this activity is presented with a largerepresentation, in particular the support given to poverty eradication program, managed byfederal and state governments. However, despite the great economic and social importance, arenot assessed the risks and environmental impacts associated with such activities. Thus, this workwas a major diagnostic companies in the region in order to identify the key attitudes harmful tothe environment. The methodology consisted in filling the spot of a questionnaire developed inorder to assess the environmental issues: the production process, the parameters of the materialbalance and the source reduction opportunity. The companies analyzed were installed in theMossoró-RN, the main city in the state (except the capital). It was found that air emissions are themajor source of pollution in these industries, despite the small size of the boilers and the fact thatmost industries are located on the outskirts of the city or the countryside. With regard to liquid waste, they are present in small amounts, and destinations appropriate given the size ofestablishments. It was noted also that neither company has a program of selective collection ofwaste.